Cultural Dimensions and Communication: An Exploratory Study Informing Agricultural and Environmental Science Graduate Student Recruitment - Allison R Byrd; Catherine Sanders; Alexa J. Lamm (Journal of Applied Communications, 2023)
The internationalization of higher education is of paramount importance because international students influence both university rankings and research capacity in STEM fields while, in colleges of agricultural and environmental sciences, they lead to global collaborations, strengthen research agendas, and increase domestic students’ intercultural competence. Recruitment strategies must consider the various cultural differences international students face and, therefore, identify communication channel preferences related to culture. However, few studies have considered differences and similarities between international and domestic graduate student communication preferences. Framed by Hofstede et al.’s cultural dimensions of collectivism-individualism, this study sought to explore the communication preferences of prospective graduate students from collectivist and individualist cultures when searching for graduate programs. Using semi-structured interviews of 10 individualist and nine collectivist participants at the University of [State] College of Agricultural and Environmental Sciences, this qualitative studied employed inductive thematic analysis to determine the communication channel use of the two groups of graduate students when searching for a graduate institution. Findings revealed participants from collectivist cultures preferred emails, departmental and lab websites, journal articles, and social media. Participants from individualistic cultures preferred emails, in-person visits, departmental and lab websites, and interpersonal communication. Implications and recommendations for future practice and research were discussed.
Keywords: cultural dimensions theory; international student communication; university communication; international student recruitment; graduate student recruitment